Software Solution Design for Photovoltaic Solar Applications. (2015) - Pasc, Petru Claudiu; Dumitru, Cristian Dragoş
Abstract: The paper presents the steps and the algorithm used to create a software for designing a solar photovoltaic application by using a programming environment in an accessible way, which provides after some calculations of all the checking required an accurate information regarding the number of series and parallel solar photovoltaic panels, currents and voltages at the string combiners, and active power flows at the photovoltaic solar panels and inverters. Due to the large number of parameters involved in the design and calculations of a solar photovoltaic application the proposal of a software solution design that allows an easy tracking of these parameters and produces a series of iterative calculations leading to the optimal solution is welcomed.